Perancangan Sistem Informasi Akuntansi Persediaan dengan Metode FIFO pada Toko A. Majid - Aisyah Lathifa; Henny Yulsiati (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Inventory is one of the key assets that supports business operations. A. Majid Store experienced several inventory management problems, including difficulties in monitoring stock availability, delays in obtaining inventory information, and time-consuming report preparation. This study aims to design an Inventory Accounting Information System using the First In, First Out (FIFO) method based on Microsoft Access. Data were collected through interviews and documentation. Based on the analysis of the existing system, a computerized inventory accounting information system was designed to manage inventory transactions, apply the FIFO method in inventory valuation, and generate inventory reports efficiently. The proposed system improves the accuracy of inventory records, accelerates information processing, and supports decision-making related to inventory management.